Metastatic large cell neuroendocrine carcinoma of larynx: Individualizing tumor biology by dual tracer positron emission tomography/computed tomography (68Ga-DOTATATE and 18F-fluorodeoxyglucose) molecular imaging and disease stabilization following 177Lu-DOTATATE peptide receptor radionuclide therapy after initial progression on chemoradiotherapy - Jadhav, Sonali; Basu, Sandip (World Journal of Nuclear Medicine, 2019)
Debate exists on the disease biology and course of primary large cell neuroendocrine carcinoma (LCNEC) of larynx, being classified as a variant of atypical carcinoid by the World Health Organisation-2005 classification, while literature of its aggressive behavior indicating poorly differentiated neuroendocrine carcinoma (akin to pulmonary LCNEC) exists. The utility of dual tracer positron emission tomography/computed tomography (68Ga-DOTATATE and 18F-fluorodeoxyglucose) in deciphering the dynamic tumor biology and feasibility of peptide receptor radionuclide therapy (PRRT) is illustrated in metastatic LCNEC of epiglottis after disease progression following conventional chemoradiotherapy. Relatively, atypical sites of soft-tissue metastases (subcutaneous tissue of arm, scrotal sac, peritoneum, and lamina of thyroid cartilage) and xiphisternum and disease stabilization following 177Lu-DOTATATE PRRT were other noteworthy unique aspects of this report.
Keywords: 177Lu-DOTATATE; 18F-fluorodeoxyglucose; 68Ga-DOTATATE; carcinoma larynx; dual tracer positron emission tomography-computed tomography; large cell neuroendocrine carcinoma; peptide receptor radionuclide therapy